Optimal operation and locating method of new energy building with shared charging service - Liu, Chang; Wang, Wei; Wang, Zhixun; Chen, Shangfa; Su, Peifang; Gao, Hongyuan; Xu, Chao; Ge, Biyuan; Ding, Hongfa; Liu, Liang (Frontiers in Energy Research, 2022)
To cope with global climate change, electric vehicles(EV) and new energy buildings are constantly being innovated and improved. With the popularity and application of big data and Internet of Things, the new energy building with available charging piles may also become a charging station, which can solve the problem of difficult charging of EVs and promote the local energy consumption of the building. Therefore, this paper proposes a shared charging concept for buildings, i.e., shared Photovoltaic, charging, energy storage building (sPCEB). Firstly, based on the analysis results of big data in cities or settlements of people, a locating method of sPCEB system is introduced, and further proposes an optimal operating strategy that maximizes the combined benefit of the building. The efficiency and effectiveness of the proposed methods are verified by simulation.